Utilization of Library Resources in Selected Public Elementary Schools - Segismundo, Mary Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the extent of utilization of library resources in selected public elementary schools in the Cainta Sub-Office, Division of Rizal, during the School Year 2025–2026. The schools included Cainta Elementary School, Arinda Elementary School, and Francisco P. Felix Elementary School Unit-I. The study focused on assessing the utilization of library resources in terms of facilities, learning materials, and services as perceived by teachers and Grade Six pupils.A descriptive survey research design was employed using a researcher-made questionnaire-checklist. The respondents consisted of 250 teachers and 289 Grade Six pupils. The sample size was determined using Slovin’s formula, and pupils were selected through simple random sampling. Teachers were profiled according to age, sex, civil status, educational attainment, length of service, position title, in-service trainings attended, and frequency of library use. Pupils were described in terms of age, sex, sibling position, family size, monthly family income, parents’ educational attainment, parents’ occupation, and frequency of library use.Findings revealed that both teachers and pupils generally utilized library resources to a great extent in terms of facilities, learning materials, and services. There was no significant difference between the perceptions of teachers and pupils regarding facilities and learning materials. However, a significant difference was found in their perceptions of library services. Moreover, no significant differences were observed in the extent of utilization when respondents were grouped according to their respective demographic profiles.The study concluded that teachers and pupils share similar levels of utilization in facilities and learning materials, while differences exist in their perceptions of library services. It is recommended that school administrators strengthen and upgrade library services, enhance facilities and learning materials, and implement an action plan to further promote effective and sustained library utilization.